Peran Media Sosial dan Primordialisme Sebagai Mobilisasi Politik Masyarakat Tanjungpinang - Dea Lestari; Aidiliza Safitri; Zalina Pitri; Sri Wahyuni (CV. ITTC INDONESIA, 2026)
This study examines the roles of social media and primordialism in the political mobilization of the community in Tanjungpinang City. Social media has become a crucial tool for disseminating political information, shaping public opinion, and enhancing civic engagement in the democratic process. Conversely, primordialism—linked to identities such as ethnicity, religion, culture, and region of origin—continues to influence the community’s political behavior. The study reveals that social media usage can accelerate the spread of political information while simultaneously amplifying the impact of group identity on political choices. Although this can boost civic engagement in politics, it may also lead to the spread of hoaxes, polarization, and identity politics if not balanced with adequate digital literacy. Consequently, to ensure that political mobilization in Tanjungpinang is conducted democratically, rationally, and based on shared interests, political education and smarter social media usage are required.